The Effect of Learning Achievement and Satisfaction with Flipped Classroom of Student in Seminar in Tourism and Hospitality Management Classroom Teaching in New Normal Life during the COVID-19 Epidemic. - Rungsattra, Chonthicha (Dusit Thani College Journal, 2022)
This research to study 1) to compare learners’ learning achievement in flipped classroom teaching through Microsoft Teams. 2) To assess the satisfaction of learners toward the inverted classroom teaching via Microsoft Teams in the Tourism and Hospitality Management Seminar Course in the first semester of the academic year 2021. This research model is mixed methods research (quantitative and qualitative). The population group is 13 students in the Department of Tourism and Hospitality Management, Year 4, Faculty of Business Administration. North - Chiang Mai University. The tools used in the research were quizzes, observational, worksheets and assessment forms. The statistics used in the data analysis were percentage, mean, and Dependent Sample t-test. Findings were as follows: 1) the findings also reflect that the teaching-learning Process of flipped classroom resulted in better scores for all students. With an average score of 9.08 standard deviation was 0.75 and when comparing the scores before and after study, it was found that the students’ test scores after school were significantly higher than before at the 0.05 level. (t = 31.22, sig. = 0.000) 2) the satisfaction assessment results found that the average level of satisfaction of students for the Seminars in tourism and Hospitality management Course are at a highest level. And the satisfaction level of the students who had a learning of flipped classroom was at the highest level as well. The outstanding findings from the observations are: Students learned about Seminar in Tourism and Hospitality Management by Online meeting 3 times during the course of the content period. The researcher has assigned the work to all students. Learn how to organize a seminar thinking of activities and advantages and disadvantages of organizing all 3 Conference and together analyzing ways to solve and prevent problems As a result, students can do learning activities in the reverse classroom and in class. By bringing the results of the analysis to discuss and planning to prepare for their own seminar to prevent and control the problem to a minimum including practicing teamwork. Including from in-depth individual interviews, it was found that students had a great understanding and satisfaction with learning management in reverse classroom activities through the Microsoft Teams in New Normal Life during the COVID-19 Epidemic.